Synergy of Carbon Nanofiber Innovation from Zinc Oxide Modified Sugar Palm Fiber as Advanced Materials for Arsenic Heavy Metal Waste Remediation - Elisabeth Nugrahini; Lina Mahardiani; Ida Setiarini; Wieke Helma Anjelina (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2022)
Heavy metal wastes cause water pollution. One of them is very toxic arsenic heavy metal waste; thus, treating them before they are released freely into the waters is necessary. In this case, the manufacture of carbon nanofibers (CNF) from sugar palm fiber waste is an innovation that can produce adsorbents to remediate heavy metals, thereby increasing the use value of sugar palm fiber waste. Carbon nanofiber from palm fiber (Arenga pinnata) was modified with ZnO metal, with varying concentrations of 0.1%, 1%, and 10%, in 1 gram of carbon nanofiber. Carbon nanofibers were made by carbonizing sugar palm fibers at 300oC for two hours. Furthermore, wet impregnation was carried out with Zn(CH3COO)2.2H2O and ended with calcination at 250oC for an hour, resulting in black nanofiber powder. This research was conducted to determine the effect of ZnO concentration on the characteristics of the carbon nanofiber produced and its effectiveness in remediating heavy metal arsenic. The ZnO/carbon nanofiber adsorbent material was then characterized using FTIR, XRD, and SEM analyses. Determination of the absorption of ZnO/carbon nanofibers on heavy metal arsenic was also assessed employing AAS analysis.